2012
DOI: 10.1155/2012/342806
|View full text |Cite
|
Sign up to set email alerts
|

Protectors or Traitors: The Roles of PON2 and PON3 in Atherosclerosis and Cancer

Abstract: Cancer and atherosclerosis are major causes of death in western societies. Deregulated cell death is common to both diseases, with significant contribution of inflammatory processes and oxidative stress. These two form a vicious cycle and regulate cell death pathways in either direction. This raises interest in antioxidative systems. The human enzymes paraoxonase-2 (PON2) and PON3 are intracellular enzymes with established antioxidative effects and protective functions against atherosclerosis. Underlying molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 72 publications
(148 reference statements)
3
77
0
1
Order By: Relevance
“…30 From such perspective, it appears worth investigating if cancer cells scavenge PON1 from the circulation to exploit its anti-oxidative effect for cell death escape. Generally, such a hypothesis might be supported by studies linking PON1 genotypes, for example, to renal carcinomas, breast, ovarian and prostate cancer (as reviewed elsewhere 31 ). However, it yet remained uncertain which function of PON1 was of major importance, its hydrolytic activity or anti-oxidative effect.…”
Section: Discussionmentioning
confidence: 92%
“…30 From such perspective, it appears worth investigating if cancer cells scavenge PON1 from the circulation to exploit its anti-oxidative effect for cell death escape. Generally, such a hypothesis might be supported by studies linking PON1 genotypes, for example, to renal carcinomas, breast, ovarian and prostate cancer (as reviewed elsewhere 31 ). However, it yet remained uncertain which function of PON1 was of major importance, its hydrolytic activity or anti-oxidative effect.…”
Section: Discussionmentioning
confidence: 92%
“…Early studies have indicated that both human and animal PON1 is closely associated with the HDL-C fraction, and this interaction is stabilised by the apolipoprotein A-I [9,39,47]. PON1 is essential for the antioxidative HDL-C protection of LDL-C [92]. On the other hand, in vitro studies have demonstrated that oxLDL-C, as well as other oxidised lipoproteins, markedly decrease the PON1 activity, thus bringing about HDL-C dysfunctionality [8].…”
Section: Paraoxonase 1 Myeloperoxidase and Hdl-cmentioning
confidence: 99%
“…However, at present it seems that both play an important role in the body's protection against atherosclerosis and systemic inflammation, but also against cancer [22,84,92].…”
Section: Paraoxonase 1 Myeloperoxidase and Hdl-cmentioning
confidence: 99%
“…An emerging strategy for cancer therapy is to overcome the resistance to apoptosis caused by aberrant Bcl-2 signaling in tumor cells (96,97). Recently, several small molecules triggering apoptosis independent of either pro-or anti-apoptotic Bcl-2 proteins have been It has been reported that lung tumor cells are resistant to conventional therapeutic drugs partially due to enhanced expression of PON2, which is thought to be associated with anti-oxidant activities of PON2 (78,79). Data presented in Figure 3.13 show decreased killing of A549 and NCI-H1299 cells with shRNA for PON2; which is consistent with previous results (9).…”
Section: Chapter 4: Discussionmentioning
confidence: 99%
“…PON2 is upregulated in many types of cancer, including lung cancer, enabling cancer cells to resist conventional therapeutic drugs (78,79). PON2 expression also prevents NHBE and hT/LT/Ras cells were grown in BEGM supplemented with SingleQuots (LONZA).…”
Section: Paraoxonase 2 (Pon2)mentioning
confidence: 99%